2018
DOI: 10.1089/apc.2018.0126
|View full text |Cite
|
Sign up to set email alerts
|

Limited Knowledge and Mixed Interest in Pre-Exposure Prophylaxis for HIV Prevention Among People Who Inject Drugs

Abstract: People who inject drugs (PWID) experience sexual and injection-related HIV risks, but uptake of pre-exposure prophylaxis (PrEP) for HIV prevention among PWID has been low. Improving PrEP uptake in this population will require understanding of PrEP knowledge and interest. In 2017, we conducted in-depth, semistructured interviews with HIV-uninfected PWID and key informants (PrEP and harm reduction providers) in the US Northeast. Thematic analysis of coded data explored PrEP knowledge and the factors that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 48 publications
7
62
1
1
Order By: Relevance
“…Moreover, our findings suggest that practitioners might be more willing to prescribe PrEP as a best first clinical step for PWID than previously indicated [11,[14][15][16]. Practitioner specialty also mattered for the PWID case vignette, as internal and family medicine practitioners were twice as likely as infectious disease practitioners to view PrEP as an important first step for PWID.…”
Section: Plos Onementioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, our findings suggest that practitioners might be more willing to prescribe PrEP as a best first clinical step for PWID than previously indicated [11,[14][15][16]. Practitioner specialty also mattered for the PWID case vignette, as internal and family medicine practitioners were twice as likely as infectious disease practitioners to view PrEP as an important first step for PWID.…”
Section: Plos Onementioning
confidence: 61%
“…Treating different priority groups also adds another layer of complexity to practitioner PrEP prescribing practices. For example, studies have found varying levels of confidence and willingness among practitioners to prescribe PrEP across patient groups, with practitioners expressing greater inclination to prescribe to MSM than to behaviorally vulnerable heterosexuals or PWID [14][15][16]. Moreover, routine risk assessments occur infrequently in primary care, which can influence practitioner prescribing of PrEP if patients are not assessed for HIV risk [11,17].…”
Section: Resultsmentioning
confidence: 99%
“…Studies focusing on PrEP awareness among PWID have shown low rates of PrEP awareness (from 13% to 31%), indicating that PrEP awareness is a significant barrier to PrEP uptake among PWID (Kuo et al, 2016;Roth, Tran et al, 2018;Sherman et al, 2019;. The lack of PrEP awareness among PWID, in general, might be attributed to the fact that past campaigns about PrEP have mostly target MSM and were not accessible to many PWID, including some MSM-PWID who may identify as heterosexual (Bazzi et al, 2018). Another barrier to PrEP awareness among PWID could be a lack of willingness to prescribe PrEP to PWID by physicians (Adams & Balderson, 2016;Edelman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another barrier to PrEP awareness among PWID could be a lack of willingness to prescribe PrEP to PWID by physicians (Adams & Balderson, 2016;Edelman et al, 2016). The lack of willingness might be attributed to competing priorities for physicians, such as the need to treat a substance use disorders or other immediate health concerns, and/or drug use stigma, such as the belief that PWID cannot adhere to medications (Bazzi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, to maximize its prevention potential, PrEP uptake among sub-populations at risk of HIV acquisition is essential. Although PrEP utilization has grown substantially since its FDA approval in 2012, PrEP awareness and access, among women and PWID in particular, are low (11)(12)(13)(14)(15). Estimates indicate that nearly 170,000 women and 73,000 PWID are clinically eligible for PrEP (16); however, the medication is underutilized, speci cally among women (17), as PrEP coverage is three times as high among men relative to women (18).…”
mentioning
confidence: 99%